Set of information technologies and their role in automation of agricultural production - V. V. Al’t (Сельскохозяйственные машины и технологии)
The modern enterprises of agrarian and industrial complex are characterized by the high level of automation of technological processes. The technological development level conformto 5th and 6th technology revolutions. The automatic and automated technologies in crop production and livestock production use data of internet technologies, Global Positioning Satellite survey and observations, mashine and tractor aggregates automated operating. The models nucleus and row of information models of agricultural objects were designed on the basis of information streams systematization. The analysis of results of simulation of biological objects, cenosises, ecosystems, agro cenosises and agroecosystems showed that the most acceptable type of model is the systemically determined dynamic model of potentially effective type. The Internet-oriented database of innovative development of institutes of an agrarian profile is designed. It contains the information about sorts, machines, mechanization means, electrification and technologies in crop production, livestock production, forage production, feed processing, crop protection, biotechnologies, mechanization, veterinary science and agricultural production processing. The database is positioned as the subject-oriented, retrieval database in web space. The list of indices to which the created architecture of the database corresponds is defined. More than 20 various databases of agricultural purpose which are used in educational process and production are created. These databases are useful to agricultural producers and also organizers of agricultural production, scientists, teachers and students. Information on key indicators of innovative products and institutes – developers of innovative solutions is provided in a basis.